SPA: a peptide antagonist that acts as a cell-penetrating peptide for drug delivery - Jingjing Song; Sujie Huang; Zhengzheng Zhang; Bo Jia; Huan Xie; Ming Kai; Wei Zhang (Taylor & Francis Group, 2020)
Although cell-penetrating peptides (CPPs) has been proven to be efficient transporter for drug delivery, ideal peptide vectors for tumor therapy are still being urgently sought. Peptide antagonists have attracted substantial attention as targeting molecules because of their high tumor accumulation and antitumor activity compared with agonists. SPA, a derivative of substance P, is a potent antagonist that exhibits antitumor activity. Based on the amino acid composition of SPA, we speculate that it can translocate across cell membranes as CPPs do. In this study, our results demonstrated that SPA could enter cells similarly to a CPP. As a vector, SPA could efficiently deliver camptothecin and plasmids into cells. In addition, our results showed that SPA exhibited low toxicity to normal cells and high enzymatic stability. Taken together, our results validated the ability of SPA for efficient drug delivery. More importantly, our study opens a new avenue for designing ideal CPPs based on peptide antagonists.